Histopathological pattern of skin cancer at tertiary referral skin health centre - Adhikari, Ram Chandra; Shah, Mahesh; Jha, Anil Kumar (Journal of Pathology of Nepal, 2019)
Background: The skin is a heterogeneous organ, capable of producing various types of skin tumors. The incidence of skin cancers, including melanoma and non-melanoma has been reported to have risen in many parts of the world. In Asian and African countries, individuals with pigmented races have a much lower incidence of skin cancers despite sunny hot weather. This study is aimed to analyze age, sex and site wise of distribution of skin cancers. Materials and Methods: The study included a total of 60 patients with histopathologically proven skin cancers from January 2015 to December 2018 in the department of pathology, DI skin health and referral centre, Kathmandu, Nepal. Results: A total of 60 cases of histopathologically proven skin cancer constituted 3.69% of total skin biopsies. Patient age ranged from 15 to 88 years with mean age being 61 years. The majority of the patients were in the age group of 61-70 yrs. The male to female ratio is 1:1.3. Basal cell carcinoma was the most common skin cancer constituting 43.4%, followed by squamous cell carcinoma (28.3%). The most common site of skin cancer is head & neck (73.3%), followed by lower extremities (8.3%). Other skin cancers were Bowen’s disease, melanoma, verrucous carcinoma, keratoacanthoma, trichilemmal carcinoma, extramammary Paget’s disease, Non-Hodgkin lymphoma and metastatic tumor. Conclusions: The most common type of skin cancer is basal cell carcinoma, followed by squamous cell carcinoma and head & neck being the commonest site.